2017
DOI: 10.1124/jpet.116.239822
|View full text |Cite
|
Sign up to set email alerts
|

Low-Volume Resuscitation for Hemorrhagic Shock: Understanding the Mechanism of PEG-20k

Abstract: Hemorrhagic shock leads to cell and tissue swelling and no reflow from compressed capillaries. Cell impermeants, including polyethylene glycol-20,000 (PEG-20k), reverse ischemia-induced cell swelling, extend low-volume resuscitation (LVR) time after shock, and increase tolerance to the low-volume state. The purpose of this study was to explore the mechanisms of action of PEG-20k containing LVR solutions. We hypothesized that PEG-20k acts as both an oncotic agent and an impermeant in the microcirculation, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…Recently, polyethylene glycol (PEG) polymers of specific molecular weight ranges have been used in crystalloid solutions to act as highly effective Low volume Resuscitation (LVR) solutions [ 2 , 8 10 ]. These polymers non-energetically move isotonic fluid from intracellular and interstitial spaces into the capillary space by osmotic flow mechanics in response to metabolic cell swelling that occurs in shocked and ischemic tissues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, polyethylene glycol (PEG) polymers of specific molecular weight ranges have been used in crystalloid solutions to act as highly effective Low volume Resuscitation (LVR) solutions [ 2 , 8 10 ]. These polymers non-energetically move isotonic fluid from intracellular and interstitial spaces into the capillary space by osmotic flow mechanics in response to metabolic cell swelling that occurs in shocked and ischemic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…PEG-20k molecules are impermeant to cells and selectively partition in the capillary and interstitial spaces in a ratio of 2:1, respectively [ 2 , 10 ]. This pulls isotonic fluid out of swollen cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEGylation has become a mainstay in biopharmaceutical production: a search of http://www.clinicaltrials.gov for studies of interventions with the keyword “PEG” revealed that there are currently 75 active (finished recruiting) trials involving a PEGylated therapeutic, and an additional 219 open studies (not yet recruiting, recruiting, or available for expanded access). Unmodified PEG alone is also under development for intravenous administration as a low‐volume resuscitation solution for hemorrhagic shock …”
mentioning
confidence: 99%
“…Unmodified PEG alone is also under development for intravenous administration as a low-volume resuscitation solution for hemorrhagic shock. 3,4 Surprisingly, animal and human studies have shown that some PEG-modified therapeutics can induce antibodies that specifically bind PEG, leading to rapid elimination, loss of efficacy, and a marked increase in risk of serious adverse events. 1,[5][6][7][8] For example, in 2016 a phase III study (NCT01848106) of a PEGylated RNA aptamer (pegnivacogin) for inhibition of coagulation factor IXa was halted following serious adverse events (SAEs) linked to anti-PEG antibody (APA) responses.…”
mentioning
confidence: 99%